FROM MARGINS TO MAINSTREAM: EVALUATING WOMEN'S ROLE IN GOVERNANCE - Suyito, Suyito; sabari, Desi emilia sari; lianjar, Edwin ferdy; kesidsettambul, Iuking; kurniawan, Uun; sari, Wirawan trisna (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
This study explores the impact of women's empowerment on their participation in governance, examining the multifaceted barriers that hinder political engagement. Through qualitative methods, including case studies and focus group discussions, the research captures the experiences of women who have navigated these challenges. The findings reveal that cultural norms, economic limitations, and institutional inadequacies significantly affect women's political involvement. Empowerment initiatives, such as educational programs and supportive networks, were found to enhance women's confidence and motivation to participate in governance. The study emphasizes the need for targeted public policies, including gender quotas and mentorship programs, to create an inclusive political environment. Ultimately, the research highlights that fostering women's empowerment is crucial for ensuring diverse representation and improving the effectiveness of governance, contributing to more equitable decision-making processes in society.